Load Frequency Control Based on Gray Wolf Optimizer Algorithm for Modern Power Systems - Dao Huy Tuan; Dao Trong Tran; Van Nguyen Ngoc Thanh; Van Van Huynh (Energies)
The increasing complexity of modern power systems (MPSs), driven by the integration of renewable energy sources and multi-area configurations, demands robust and adaptive load frequency control (LFC) strategies. This paper proposes a novel approach to the LFC of the MPS by integrating a proportional–integral–derivative (PID) controller optimized using the gray wolf optimizer (GWO) algorithm. The effectiveness of the GWO-PID method is evaluated on multi-area power systems, including systems integrated with wind energy. The GWO-PID controller shows superior frequency stability, achieving deviations of 49.67 Hz, 49.68 Hz, 49.87 Hz, 49.87 Hz and 49.88 Hz for area 1 and area 2 of the two-area multisource MPS, as well as for area 1, area 2 and area 3 in the three-area multisource MPS. The results demonstrate significant improvements in frequency stabilization, reduced oscillations and enhanced steady-state accuracy compared to traditional optimization techniques. This study emphasizes the scalability and adaptability of the proposed method to changing load conditions and complexity of the MPSs, providing a potential solution to ensure stability and reliability for the MPSs.